Influence of Guided Imagination on Pain Intensity in Fracture Patients at Bumiayu Regional Hospital - Ahmad Zakiudin; Tati Karyawati; Ismi Roikhatul Janah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
SA survey by the Indonesian Ministry of Health found that 25% of fracture sufferers died, 45% experienced physical disabilities, 15% experienced psychological stress due to anxiety and even depression and 10% recovered well. Both open and closed fractures will affect nerve fibers which can cause pain and discomfort. Efforts that can be made to reduce pain in fracture patients are with one of the non-pharmacological techniques, namely guided imagination. The aim of this research is to determine the effect of guided imagination on reducing pain intensity in fracture patients at Bumiayu Hospital 2024. The type of research is Quasi Experiment research with a One Group Pre-test Post-test design. The population in this study were all fracture patients at Bumiayu Regional Hospital in the period 4 March - 2 April 2024, totaling 52 people and the sample was taken using a purposive sampling method, namely 35 people. Data collection used a numerical scale research instrument sheet or The Pain Numerical Rating Scale (PNRS). The data analysis used is univariate and bivariate analysis. The results of this study show that statistical analysis showed that the difference in average pain intensity in fracture patients before guided imagination was 6.83 and after guided imagination was 3.46 with a probability value of (p=0.000), so Ho was rejected and Ha was accepted, meaning that guided imagination had an effect on reducing the intensity. pain in fracture patients. In conclusion, there is an effect of providing guided imagery on pain intensity in fracture patients at Bumiayu Regional Hospital in 2024.